Pharmaceutical Storage Management and Its Impact on Medication Obsolescence: A Case Study of Nizam Farma Pharmacy in 2025 - Iqbal Julian; Lusiana Ariani; Revalin Changestu (Faculty of Pharmacy Universitas Pancasila, 2026)
This evaluative study investigates the pharmaceutical storage management system at Nizam Farma Pharmacy to determine its degree of adherence to the Indonesian Ministry of Health (MOH) Regulation No. 73 of 2016 and the associated technical guidelines. A descriptive quantitative observational design was employed, utilizing a comprehensive 23-variable checklist for direct-site auditing. In addition to observational data, a secondary analysis of the facility’s 2024 medication expiration logs was conducted to identify obsolescence profiles of the medications. The pharmacy attained a compliance index of 0.80, correlating to the